VEGETABLE FARMER BEHAVIOR ANALYSIS IN PURCHASING INSECTICIDES (Case Study In Vegetable Farmers in Sungai Selamat Siantan Hilir District) (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2013)
Vegetable Farmer Behavior Analysis in Purchasing insecticides (Case Study In Vegetable Farmers in Sungai Selamat Siantan Hilir District) The objectives of this study were: 1) determine the behavior of vegetable farmers in the purchase of insecticides based on product attributes in Sungai Selamat Siantan Hilir District and 2) identify the product attributes that taken into consideration in the purchase of insecticide. The research was conducted on vegetable farmers in the Sunagi Selamat Siantan hilir district North Pontianak within sampling by simple random sampling. Observed variables are variables which consists of consumer behavior and beliefs purchase evaluation based insecticide product attributes that include price, quality, volume and packaging manufacturer's instructions indicated on the package label. It also investigated behavior is also influenced by external factors which include variable normative beliefs and motivation variables. Analysis of research data using the model of Fishbein multiatribut. Fishbein multi-attribute analysis results indicate that the value of a vegetable farmer attitudes to insecticide products is good on all three insecticides used are derived from the manufacturer Syngenta, Dupont and DGW. Quality attributes against insect pests of the class to be a major consideration in the purchase of the three insecticides. Keywords: Consumer Behavior, Vegetable Farmers, Purchasing insecticides.